2022
DOI: 10.1186/s13018-022-03109-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute shortening and re-lengthening versus antibiotic calcium sulfate-loaded bone transport for the management of large segmental tibial defects after trauma

Abstract: Background The purpose of this paper was to compare the clinical effects of acute shortening and re-lengthening (ASR) technique with antibiotic calcium sulfate-loaded bone transport (ACSBT) technique for the management of large segmental tibial defects after trauma. Methods In this retrospective study, 68 patients with large segmental tibial defects were included and completely followed. The bone loss was 3–10 cm. ASR group included 32 patients, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Due to the nature of the intervention, all patients in the planned intervention group were treated by bone transport, whereas some in the observed group underwent acute shortening and re-lengthening (ASR) [ 33 , 35 , 37 , 38 , 41 ]. Outcomes were therefore compared only for those patients treated without routine docking site intervention (observed group) between those managed by ASR or bone transport.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the nature of the intervention, all patients in the planned intervention group were treated by bone transport, whereas some in the observed group underwent acute shortening and re-lengthening (ASR) [ 33 , 35 , 37 , 38 , 41 ]. Outcomes were therefore compared only for those patients treated without routine docking site intervention (observed group) between those managed by ASR or bone transport.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies in the observed group reported the use of either poly-methyl methacrylate or calcium sulphate bone cement within the defect (54 patients) [ 22 , 37 ]. The rationale for this is to induce a biologically active membrane to assist union and regenerate formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of bone regeneration in the distraction area relies on several factors, including osteoinductivity, osseointegration, angiogenesis of the callus, and the biomechanical environment (Inan et al,2005;Borzunov,2012;Bezstarosti et al,2021;Huang et al,2022). Published studies (Ai-Aql et al, 2008;Sojo et al,2005;Morgan et al,2012;Pacicca et al,2003) have shown that DO triggers a more intense angiogenic response compared to normal fracture healing, with neovascularization growing in the same direction as the primary mineralization front.…”
Section: Discussionmentioning
confidence: 99%